Evaluation of Satellite-Derived Bathymetry from High and Medium-Resolution Sensors Using Empirical Methods - Evagorou, Evagoras S.; Argyriou, Athanasios V.; Papadopoulos, Nikos G.; Mettas, Christodoulos; Alexandrakis, George; Hadjimitsis, Diofantos G. (My University, 2022)
This study evaluates the accuracy of bathymetric maps generated from multispectral satellite datasets acquired from different multispectral sensors, namely the Worldview 2, PlanetScope, and the Sentinel 2, in the bay of Elounda in Crete. Image pre-processing steps were implemented before the use of the three empirical methods for estimating bathymetry. A dedicated correction and median filter have been applied to minimize noise from the sun glint and the sea waves. Due to the spectral complexity of the selected study area, statistical correlation with different numbers of bands was applied. The analysis indicated that blue and green bands obtained the best results with higher accuracy. Then, three empirical models, namely the Single Band Linear Algorithm, the Multiband Linear Algorithm, and the Ratio Transform Algorithm, were applied to the three multispectral images. Bathymetric and error distribution maps were created and used for the error assessment of results. The accuracy of the bathymetric maps estimated from different empirical models is compared with on-site Single beam Echo Sounder measurements. The most accurate bathymetric maps were obtained using the WorldView 2 and the empirical model of the Ratio Transform algorithm, with the RMSE reaching 1.01 m.
Keywords: Closed bay; Multi-band linear algorithm; PlanetScope; Ratio transform algorithm; Satellite-derived bathymetry; Sentinel 2; Single linear algorithm; Turbidity; Worldview 2